Sargassum sp. Growth Cultivated with Different Seed Weights on Floating Raft System in Ekas Bay East Lombok - Safitri, Wiwin; Cokrowati, Nunik; Diniarti, Nanda (Jurnal Perikanan dan Kelautan, 2021)
Sargassum sp. is seaweed from the group of brown algae belonging to the Phaecophyceae class that can be found in Indonesian. Sargassum sp. contains polysaccharides in the form of alginate which can be used as raw materials and additives in the food, drug, and cosmetic industries. The aim of this study was to analyze the growth of Sargassum sp. which are cultivated with different seed weights on the floating rafts. The research was conducted from November 2020 to March 2021 in Ekas Bay, East Lombok, West Nusa Tenggara. The research method used is an experimental method using a completely randomized design (CRD) consisting of five treatments with four replications. The treatments were differences in the weight of the initial seeds used, namely treatment A (25 g), B (50 g), C (100 g), D (150 g), and E (200 g). Sargassum sp. Cultivation was carried out for a month. The results were the highest absolute weight was in treatment E with 550 g and the lowest occurred in A with 262.5 g. The highest specific growth was in treatment A with 8.13%/day and the lowest was in E with 4.4%/day. This study concluded that different seedling weights had a significant effect on the growth of Sargassum sp. cultivated using the floating raft method